Cigarette Smoking and Measures of Impulsivity in a College Sample. Issue 3 (July 2013) - Balevich, Emily C.; Wein, Naftali D.; Flory, Janine D.
Background: An association between impulsivity and smoking has been consistently reported in the literature, but few studies have examined how distinct dimensions of impulsivity may relate differentially to smoking initiation versus persistent smoking. The aim of the current study was to examine the relationship between self-report and behavioral measures of impulsivity and smoking status in college students. Methods: Participants ( N = 243) completed a self-report history of tobacco use, 2 self-report measures of impulsivity (the Barratt Impulsiveness Scale and Zuckerman Sensation-Seeking Scale), and 2 behavioral measures (the Delay Discounting Task and Iowa Gambling Task). All participants were classified as never-smokers, triers, or smokers based on their smoking history, and between-group differences on the 4 measures were examined. Results: On the self-report measures, all 3 groups differed on sensation seeking, with the never-smokers reporting the lowest levels and the smokers reporting the highest. Furthermore, the smokers reported significantly higher disinhibitory impulsivity than the triers and never-smokers. The groups did not differ on the behavioral measures. Conclusions: These results indicate that distinct dimensions of impulsivity characterize different smoking phenotypes. In particular, sensation seeking is associated with the initiation of smoking, whereas disinhibitory impulsivity is associated with the transition to more persistent and regular use of cigarettes.